Analgesic Impact of a Popliteal Plexus Block to Standard Adductor Canal Block in Arthroscopic Anterior Cruciate Ligament Reconstruction: A Randomized Blind Clinical Trial - Atef Mahmoud; Maged Boules; Joseph Botros; Mohamed Mostafa; Safaa Ragab; Mohammed Alsaeid (Pain Research and Management)
Background. Damage to the anterior cruciate ligament (ACL) is crippling and often requires an arthroscopic outpatient surgery. Nevertheless, many patients experience severe pain during the first day after ACL reconstruction (ACLR). The adductor canal block (ACB) has yielded conflicting results for post-ACLR pain relief. This research investigated the effect of a supplemental popliteal plexus block on postoperative pain outcomes compared to a sole ACB. Methods. Following a randomized design, 60 cases scheduled for knee arthroscopy with ACLR using an ipsilateral hamstring graft were separated into two categories. Subjects in group A (n = 30) received an ACB only, while subjects in group B (n = 30) received combined ACB and popliteal plexus block (PPB). Results. We found significant differences between the two groups. The time of the first analgesic request (TFR) was later for the combined ACB and PPB (median 8 h) compared to the ACB only group (median 0.5 h). Morphine consumption was lower for patients who received combined ACB and PPB (median 12 mg) compared to ACB only (median 30 mg). The number of the requested doses was lower for the combined ACB and PPB group (median 3 doses) compared to the ACB only group (median 7 doses). Conclusions. The addition of PPB to ACB was associated with improved analgesia and a reduced need for opioid-based sedatives following ACLR with an ipsilateral hamstring graft (https://clinicaltrials.gov/ct2/show/NCT04020133).